Relationship Of Occupational Stress, Burnout And Coping Strategies Of Pakistani Female Private School Teachers: Social Work Perspective - Shah, Syed Fasiha (2023)
The present research study aimed to assess occupational stress, factors causing stress, coping strategies adapted by female teachers to deal with occupational stress.